An Overview of Live Attenuated Recombinant Pseudorabies Viruses for Use as Novel Vaccines - Bo Dong; Dante S. Zarlenga; Xiaofeng Ren (Journal of Immunology Research)
Pseudorabies virus (PRV) is a double-stranded, DNA-based swine virus with a genome approximating 150 kb in size. PRV has many nonessential genes which can be replaced with genes encoding heterologous antigens but without deleterious effects on virus propagation. Recombinant PRVs expressing both native and foreign antigens are able to stimulate immune responses. In this paper, we review the current status of live attenuated recombinant PRVs and live PRV-based vector vaccines with potential for controlling viral infections in animals.